Study on the compliance of nutrition labels on prepackaged food according to local and international guidelines / Kok Sing Chuan - Kok , Sing Chuan (2017)
Nutrition information on food labels acts as a conduit for food producers to convey related information to consumers. Nutrition labels are available on mostly all prepackaged foods in the market. Some researches showed that credible nutrition labels for consumers are able to assist consumers in making a healthier choice. The objectives of this study are to investigate the accuracy of nutrition label at prepackaged foods in Malaysia and how many prepackaged foods do not comply with the local and international guidelines. Another objective is to study the current enforcement practice for nutrition labelling regulations in selected hypermarkets and governmentï¿½s authority in this matter. The present study consists of 100 samples which have been stratified into eight categories which are prepared cereal food; milk and dairy products; flour confection; canned meat, fish and vegetables; canned fruit and various fruit juices; snacks and indulgence food; coffee, tea and other beverages; and spread. Laboratory analysis has been carried out to determine the content of energy, fat, carbohydrate and protein in the samples. The analytical values are compared with the declared values by referring to the guidelines, in order to determine the percentage of compliance. Additionally, interview sessions with person in charge from both the government and private sectors are conducted to get information about common practice of surveillance of nutrition labelling accuracy. The results have shown that 34% of analysed products do not comply with the tolerance limit according to the Food Act 1983, Malaysia (one-way approach tolerance limit). Moreover, 73% of the products failed to comply with the tolerance leeway Â± 20% (two-way approach) and 56% of products do not comply with the tolerance limits set in Local Authority Coordinator Regulatory Services (LACORS). Canned meat, fish and vegetables illustrated the worst percentage of compliance among all food categories, in other words protein demonstrated the highest percentage of non-compliance. Based on the interview sessions, there is no specific practice to ensure the accuracy of the nutrition labels on the packaged food sold in the markets. The poor accuracy of nutrition label on prepackaged food based on this study requires reassessment by the manufacturers. It is also suggested, an enforcement unit to be set up and conduct unscheduled surveillance on the accuracy of nutrition label as a trustworthiness control. In addition, food manufacturers can also send their products to accredited laboratories to get more accurate and precise nutrition information. The government may give tax relief for food manufacturers on this analytical service cost. Consequently, consumers will be able to gain credible food products. Lastly, further investigation regarding the accuracy of other nutrients such as sodium, trans fat, contents of nutrients or minerals which have been declared on the package food must also be tested in future studies.